2022
DOI: 10.1038/s41420-022-00974-x
|View full text |Cite
|
Sign up to set email alerts
|

N6-isopentenyladenosine induces cell death through necroptosis in human glioblastoma cells

Abstract: Targeting necroptosis is considered a promising therapeutic strategy in cancer, including Glioblastoma Multiforme (GBM), one of the most lethal brain tumors. Necroptosis is a mechanism of programmed cell death overcoming the apoptosis resistance mechanism underlying GBM tumorigenesis and malignant progression. N6-isopentenyladenosine (iPA), adenosine modified with isoprenoid derivative, displays antitumor activity in different cancer models. In previous studies, we demonstrated that iPA interferes with EGFR si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…144 Pagano et al identified a natural novel necroptosis agonist, N6-isopentenyl adenosine (iPA), which induced only necroptosis and no apoptosis in primary glioblastoma cells. 148 Following iPA treatment, higher p-RIPK1/3 and p-MLKL levels were detected, and Nec-1s was observed to rescue cells from necroptosis. Abdel-Salam et al discovered a synthetic peptide, LyeTxI-b, that engendered cytotoxicity against glioblastoma cells by primarily inducing necroptosis and, hence, was a potential novel prototypic cell model.…”
Section: Zika Virus and West Nile Virusmentioning
confidence: 97%
See 2 more Smart Citations
“…144 Pagano et al identified a natural novel necroptosis agonist, N6-isopentenyl adenosine (iPA), which induced only necroptosis and no apoptosis in primary glioblastoma cells. 148 Following iPA treatment, higher p-RIPK1/3 and p-MLKL levels were detected, and Nec-1s was observed to rescue cells from necroptosis. Abdel-Salam et al discovered a synthetic peptide, LyeTxI-b, that engendered cytotoxicity against glioblastoma cells by primarily inducing necroptosis and, hence, was a potential novel prototypic cell model.…”
Section: Zika Virus and West Nile Virusmentioning
confidence: 97%
“…Nec-1 is reportedly the first RIPK1 inhibitor, 1 along with Nec-1s, which has been widely used in mechanism research. 64,106,148,161,167 The crystal complex of the RIPK1 kinase with Nec-1, Nec-3, and Nec-4 revealed the structural basis of necrostatin-mediated RIPK1 inhibition for precise drug design. 179 According to the binding modes, RIPK1 inhibitors can be categorized as type I, II, and III inhibitors, 180 and some of them have entered clinical trials (discussed in our recent review 181 ).…”
Section: Necroptosis Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter scenario, necroptotic cancer cells not only attract myeloid-derived suppressor cells and/or tumor-associated macrophages and cause tumor-associated immune suppression but also release cytokines that promote angiogenesis, cancer proliferation, and metastasis (11).Necroptosis is considered to be a promising strategy in treatment evaluation of a broad spectrum of tumors (7, 12). Pagano et al reported that N6isopentenyladenosine could bypass the apoptosis resistance mechanism and induce necroptosis in GBM cells thereby offering higher therapeutic efficacy (13). However, the exact role of necroptosis in glioma has remained relatively underresearched.…”
Section: Introductionmentioning
confidence: 99%
“…Pagano et al. reported that N6-isopentenyladenosine could bypass the apoptosis resistance mechanism and induce necroptosis in GBM cells thereby offering higher therapeutic efficacy ( 13 ). However, the exact role of necroptosis in glioma has remained relatively under-researched.…”
Section: Introductionmentioning
confidence: 99%